Global transcriptome modulation by xenobiotics: the role of alternative splicing in adaptive responses to chemical exposures - Andrew J. Annalora; Jacki L. Coburn; Antony Jozic; Patrick L. Iversen; Craig B. Marcus (Human Genomics)
Abstract Background Xenobiotic exposures can extensively influence the expression and alternative splicing of drug-metabolizing enzymes, including cytochromes P450 (CYPs), though their transcriptome-wide impact on splicing remains underexplored. This study used a well-characterized splicing event in the Cyp2b2 gene to validate a sandwich-cultured primary rat hepatocyte model for studying global splicing in vitro. Using endpoint PCR, RNA sequencing, and bioinformatics tools (rSeqDiff, rMATs, IGV), we analyzed differential gene expression and splicing in CYP and nuclear receptor genes, as well as the entire transcriptome, to understand how xenobiotic exposures shape alternative splicing and activate xenosensors. Methods Primary rat hepatocytes in sandwich culture were exposed to two methylenedioxybenzene (MDB) congeners and carbamazepine, with gene expression and splicing assessed. A 3D-clustergram integrating KEGG pathway analysis with differential gene expression provided distinct splicing landscapes for each xenobiotic, showing that splicing diversity does not always align with gene expression changes. Results Endpoint PCR revealed a Cyp2b2v to wild-type Cyp2b2 splicing ratio near 1:1 (100%) under most conditions, while RNA-seq showed a stable baseline closer to 40%. C6-MDB reduced this ratio to ~ 50% by PCR and ~ 39% by RNA-seq, showing slight method-dependent variations yet consistent trends. In contrast, exon 6 skipping in Cyp1a1 occurred only with MDB exposure, implicating AHR activation. Xenobiotic treatments also induced alternative splicing in defensome and stress-responsive genes, including the phase II enzyme Gstm3, Albumin, Orm1, and Fxyd1, highlighting their roles in xenobiotic response modulation. Significant splicing changes in factors such as SRSF1, SRSF7, and METTL3 suggest a coordinated feedback loop involving epitranscriptomic modulation and cross-talk within SR protein networks, refining splice site selection, transcript stability, and cellular fate. Conclusions This study demonstrates how xenobiotic structural features influence gene expression and splicing, revealing splicing patterns that expand our understanding of transcriptome diversity and function. By identifying regulatory mechanisms, including AHR activation, epitranscriptomic modulation, and crosstalk within SR protein networks, that shape adaptive responses to xenobiotic stress, this work offers insights into the splicing and transcriptional networks that maintain cellular homeostasis. These findings provide predictive biomarkers for toxic exposures and highlight the potential of splicing profiles as diagnostic tools for assessing the health impacts of chemical exposure.